1987
DOI: 10.1099/0022-1317-68-8-2069
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Epstein-Barr Virus Strain Variants in Lymphoblastoid Cell Lines 'Spontaneously' Derived from Patients with Rheumatoid Arthritis, Infectious Mononucleosis and Normal Controls

Abstract: SUMMARY'Spontaneous' lymphoblastoid cell lines (LCL) were established from patients with either rheumatoid arthritis (RA) or infectious mononucleosis (IM) or from healthy donors. Differences in Epstein-Barr virus (EBV) strains were determined by measuring the mol. wt. and expression of viral antigens in each of the LCLs. In addition to the previously reported EBV nuclear antigens, the LCLs also contained EBV-induced antigens with tool. wt. of 48K and 58K which were present in all but two of the lines. One of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 22 publications
(21 reference statements)
1
10
0
Order By: Relevance
“…Thus, type A virus may be further differentiated as A-C or A-D according to polymorphism of the BamHI I region of the viral genome. Using the regions of genetic polymorphism as epidemiological markers, we observed a great deal of heterogeneity among natural EBV strains associated with IM patients and healthy individuals, confirming earlier studies on recently established LCLs (22,28). In a university community, viruses of several genotypes are circulating simultaneously.…”
Section: Fig 4 (A) Schematic Representation Of B95-8 W91supporting
confidence: 85%
“…Thus, type A virus may be further differentiated as A-C or A-D according to polymorphism of the BamHI I region of the viral genome. Using the regions of genetic polymorphism as epidemiological markers, we observed a great deal of heterogeneity among natural EBV strains associated with IM patients and healthy individuals, confirming earlier studies on recently established LCLs (22,28). In a university community, viruses of several genotypes are circulating simultaneously.…”
Section: Fig 4 (A) Schematic Representation Of B95-8 W91supporting
confidence: 85%
“…As already discussed, little is known of the biological implications of genomic differences in EBV isolates studied thus far. There are data showing that there may be naturally occurring transforming defective EBV isolates similar to HR-1 EBV [Alfieri and Joncas, 19871, and that there are antigenic differences between surface and envelope structural polypeptides of HR-1 and B95-8 viruses [Mueller-Lantzsch et al, 19811. There are also recent data showing differences in EBNA-1 and EBNA-2 products, as well as polymorphism in different clinical isolates [Sculley et al, 1987;Katz et al, 19881. Our results demonstrate that there are antigenic and electrophoretic differences in the DNases induced by different isolates of EBV. These results suggest that there may be differences in the amino acid composition and/or structure of these enzymes, and that there is biological variation between these strains of EBV.…”
Section: Discussionmentioning
confidence: 97%
“…A variety of wild-type EBV strains exist in the general population. However, similarities in a number of LCLs suggest that the diversity of wild-type strains may be limited (Sculley et al 1987). Gratama and colleagues observed that most unrelated individuals carry a single and distinctive Ebnotype.…”
Section: Ebnotypingmentioning
confidence: 99%